Implementation of internal case study methods improving innovation and thinking abilities critical Courses of Micro Economics - Hodijah, Siti; Hastuti, Dwi (Jurnal Paradigma Ekonomika, 2022)
The purpose of this study is to try a method that is useful for improving students ' critical thinking skills towards students surrounding problems, the method is a case study method. Students can actualize and practice Microeconomics 1 in analyzing markets types well. With the learning outcomes of this course , the implementation of the Semester Learning Plans (RPS) with the Outcomes Based Education (OBE) model in the Development Economics study program, Faculty of Economics and Business, will be even better in the future . For this reason , it is necessary to change the OBE- based course learning system with a project-based learning approaches in the form of a case method outside the classroom. Microeconomics 1 course, in fact, encounter many problems , namely , in general, students perceive the subject of supplies and demand relations US boring and less attractive to students. In addition, students are less capable to express opinions systematic both orally and in writing and students are also less accustomed to differing opinion , debating and making the best decisions for themselves and others . The results of the analysis of the findings prove that the use of the cases study method in the micro economics relations course can improve students ' critical thinking skills , the cases study method can increase students enthusiasm in attending supplies and demand relations courses, and the use of the case studies method can create a democracy atmosphere in international relations course.